(untitled) (American Journal of Technology and Applied Sciences, 2023)
In the tapestry of technological innovation, few threads have woven a narrative as compelling and transformative as Virtual Reality (VR). Beyond the realms of screens and keyboards, VR extends an invitation to explore immersive experiences that redefine our digital interactions. This article embarks on a journey through the evolution, applications, challenges, and promises of Virtual Reality, shedding light on the dimensions that make this technology a herald of a new era.